Trail Mix - (:unkn) unknown (My University, 2019)
Trail Mix is a book of poems comprised of two sequences: “Trail Mix,” which considers the fact and aftermath of the Trail of Tears and “Red Dead Redemptions,” which utilizes the lyric narrative to consider contemporary mixedblood life. The two sequences comprising Trail Mix harmonize in dissonance: “Trail Mix” is serious, “Red Dead Redemptions” slightly playful; “Trail Mix” is historically entrenched, “Red Dead Redemptions” documents the unspooling present moment. Both interrogate what it might mean to be Cherokee. Aesthetically, the poems in the “Trail Mix” section have more movement and white space, which aligns with a major theme in the section: walking. The poems in “Red Dead Redemptions” are tighter, with less white space, reflecting the immediacy of the present moment in which they take place. Together, the sections strive to comprise a complex vision of Cherokee postindian life and thought.
Keywords: Cherokee poetry; Lyric narrative poetry; Native American poetry; Trail of Tears